PERANCANGAN SISTEM PAKAR MENDETEKSI KERUSAKAN PADA MESIN MOBIL TOYOTA AVANZA DAN RUSH STUDI KASUS CEMPAKA MAS AUTOSERVIS - Aditya, Sigit Birowo (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Along with the times, computers are widely used in various fields. For example in the fields of automotive, health and so on. One of the utilization of technology that it can be used as an expert system. One implementation of expert systems in the automotive field is to know the problems in the engine. The problems that exist in the user manual Toyota is a Toyota less know about how to care and repair engine components present in Toyota car, Toyota symptoms data often is not known at all by the user so that the user's Toyota car Toyota's detriment users itself.An expert system is a branch of artificial Intelligence that make extensive use of specialized knowledge for problem solving by an expert human level and is designed to mimic the expertise of an expert in answering questions and solving problems in all areas. The basic concept of an expert system consists of several elements of expertise, experts, recognition of expertise, and the ability to explain the rules.The method used in this study is an analysis method that uses UML (Unified Modeling Language). Meanwhile, the software created using the programming language PHP (PHP Hypertext Preprocessor) with the MySQL database system.The results of this study is a useful system for analysis and decision-making to help knowing the context of a car engine. In addition, this system serves to minimize the damage error analysis done by the engine mechanics.The conclusion of this study is the program can be used by mechanics and Toyota car users to learning the diagnose process of Toyota car damage.Â Keywords: Expert System, PHP, MySQL